Síntese de CuNb2O6 pela rota de autocombustão e imobilização em membrana de quitosana para degradação de azo corante - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
With the increase in population and the high rate of industrialization worldwide, it is necessary to advance measures to preserve the environment, water and energy resources. Furthermore, seek technologies to mitigate damage caused to the environment. Therefore, this work presents the description of the CuNb2O6 photocatalyst, orthorhombic (900 oC) and monoclinic (650 oC), by the self-combustion method, and its immobilization in a chitosan membrane by the casting method. In addition to evaluating the photocatalytic capacity in the manipulation of the yellow dye Tartrazine, widely used in the food industry. Characterizing the immobilized orthorhombic CuNb2O6 (900 oC) allowed us to verify a bandgap equal to 1.45 eV, orthorhombic structure with high purity 99.90%. Statistical analysis was carried out with the support of the Doehlert matrix to study the influence of pH and CuNb2O6 concentration during the photocatalytic reaction in the degradation of the dye, with results pointing to pH conditions equal to 7.34 and CuNb2O6 concentration equivalent to 2.27 g L-1. It proved to be efficient and promising in degradation, with an associative process between adsorption and photodegradation, with a 94% reduction in chromophoric compounds (430 nm) and an 86% reduction in aromatic compounds (260 nm) under visible radiation from the Hg lamp (filtered by the quartz bulb). The next step was to reduce the synthesis temperature and modify the radiation sources to elucidate the behavior of CuNb2O6/chitosan in the degradation of the dye to reduce energy costs. The characterization of monoclinic CuNb2O6 (650 oC) showed high purity and homogeneity, a bandgap equal to 1.48 eV, a surface area equivalent to 16.31 m2 g-1, with a wide cationic range. The degradations showed satisfactory results with reduction rates for UV LED equal to 99.37% and 80.13% for chromophoric (430 nm) and aromatic (260 nm) compounds, respectively; for Vis LED, the results were equal to 93.17% and 78.56% for chromophoric and aromatic compounds respectively and for solar radiation, the results were 85.35% and 40.89% for chromophoric and aromatic compounds respectively. After treatment, no concentrations of phenols and amines were found above the detection limit (0,5 μg L-1 e 0,25 mg L-1, respectively). Immobilization can be verified by characterization, and its stability by reusing the membranes in 6 study cycles. Leaching studies using atomic absorption analysis did not show a high concentration of leached copper in all treatments developed (maximum of 18.11 μg L-1), in addition to a very similar reaction behavior between the materials (orthorhombic and monoclinic) in the different light sources.
Keywords: Síntese; Imobilização; Associação fotocatalise/adsorção; Otimização; Reator solar; Synthesis; Immobilization; Photocatalysis/adsorption association; Optimization; solar reactor; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA